PROSES PEMBELAJARAN KARAKTER TOLERANSI DI SEKOLAH DASAR : PENELITIAN KUALITATIF PADA PESERTA DIDIK KELAS V DI SD NEGERI KRAGILAN 3 - Uminur Qoriah Ulfa; Ujang Jamaludin; Istinganatul Ngulwiyah; Encep Andriana (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study was to find out how the process of learning the character of tolerance is through the learning process, to find out how the process of learning the character of tolerance is through the activities of the learning process, to find out how to learn the character of tolerance through religious activities. This study uses a qualitative research approach with a descriptive type of research. The subjects of this study were fifth grade A teachers and fifth grade B teachers, representatives of fifth grade A students and fifth grade B students at SD Negeri Kragilan. Data collection techniques used in this study were interviews, observation and documentation. The data analysis technique used in this research is data analysis by Miles and Huberman, namely collecting data, reducing data, displaying data and drawing conclusions. The data validity technique used in this research is source and technique triangulation. The results showed that SD Negeri Kragilan 3 had implemented the implementation of the value of tolerance in learning activities and outside learning. The example of implementing the value of tolerance in learning activities is like the teacher always inserts the value of tolerance in learning activities. While the implementation of the cultivation of tolerance outside of learning is as follows, scout extracurricular, tadarus every Friday, the Prophet's Birthday event, getting used to shaking hands with the teacher before entering class. Meanwhile, the obstacles to implementing the value of tolerance in SD Negeri Kragilan 3 are divided into two, namely in learning activities and outside learning activities. In learning activities include competency and curriculum barriers, while outside learning include family environment barriers